Studi Karakterisasi Tanah Terkontaminasi Minyak Berat - Sopiah, Nida; Aviantara, Dwindrata Basuki (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2019)
ABSTRACTThe study of the characteristics of hazardous and toxic waste materials from samples of heavy oil contaminated soil containing Total Petroleum-Hydrocarbon (TPH) with a range between 1 - 2%. This study aimed to evaluate the hazard category of heavily oil contaminated soil based on organoleptic test results and Toxicity Characteristic Leaching Procedure (TCLP). Organoleptic tests carried out include explosive, igniteable, reactive (reactive) and corrosive (corrosive) and potentially toxic through TCLP. Leaching tests performed by using method based of the United States Environmental Protection Agency (US EPA) SW 846-1311. Based on the results of organoleptic observations, the samples contaminated with heavy oil that were studied did not fulfill the elements that were required to be classified as hazardous waste category 1. Meanwhile, based on TCLP test results, there were 5 parameters of heavy metals (As, Be, Cd, Pb and Se) as well as 2 organohalogen parameters (Aldrin + Dieldrin, and Vinyl Chloride) whose results are inconclusive because the quality standard values are below the detection limit of the determination method for the seven parametersKeywords: Heavy oil contaminated soil, Organoleptic test, Toxicity Characteristic Leaching Procedure, TPH 1-2%ABSTRAKTelah dilakukan studi karakteristik limbah bahan berbahaya dan beracun dari sampelÃ‚Â tanah terkontaminasiÃ‚Â minyak berat mengandung TPH dengan kisaran antara 1 Ã¢â‚¬â€œ 2%. Tujuan dari studi ini adalah untuk mengevaluasi kategori bahaya dariÃ‚Â tanah yang terkontaminasi minyak berat berdasarkan data hasil uji organoleptik dan TCLP.Ã‚Â Uji organoleptik yang dilakukan meliputi uji kemudahan meledak (explosive), menyala (igniteable), perilaku reaktif (reactive) dan korosif (corrosive) serta potensial toksik melalui uji pelindian karakteristik beracunÃ‚Â (Toxicity Characteristic Leaching Procedure Ã¢â‚¬â€œ TCLP). Uji pelindian dilakukan dengan mengacu kepada United State Environmental Protection AgencyÃ‚Â (US EPA) SW 846-1311. Berdasarkan hasil pengamatan organoleptik sampelÃ‚Â tanah terkontaminasiÃ‚Â minyak berat yang dikaji tidak memenuhi unsur-unsur yang menjadi persyaratan untuk digolongkan sebagai limbah B3 kategori 1, sedangkan berdasarkan hasil uji TCLP, terdapat 5 parameter logam berat (As, Be, Cd, Pb dan Se) serta 2 parameter organohalogen (Aldrin + Dieldrin, dan Vinyl Chloride) yang hasilnya adalahÃ‚Â inconclusiveÃ‚Â dikarenakan nilai baku mutunya berada di bawah limit deteksiÃ‚Â dari metode penetapan untuk ketujuh parameter tersebut.Ã‚Â Kata kunci: Tanah terkontaminasiÃ‚Â minyak berat, TPH 1-2%, uji organoleptik, uji pelindian karakterisitik beracunÃ‚Â